Data aggregation based on the privacy-preserving element in wireless sensor networks - Wei-ni ZENG; Ya-ping LIN; Shi-ming HE; Jian-ping YU (Tongxin xuebao)
A distributed mechanism was proposed to protect the data privacy during the data aggregation phase.The contributions of this mechanism are:1) Privacy-preserving element taking advantage of the algebraic properties of congruence was defined.In privacy-preserving elements,privacy data could be preserved without the extra data exchange,and the aggregation result could be recovered from the perturbed data in the cluster head.2)A flexible method for generating the privacy-preserving element was given.Thus,nodes could generate their privacy-preserving element without the extra data exchange,and the method was adapted to the dynamic reporting nodes.Extensive analysis showed that:compared with the centralized mechanism,the proposed mechanism has a better resistance to data loss,can avoid the single point problem and also consumes less communication overhead; compared with the other distributed mechanisms,the proposed mechanism is able to preserve privacy more efficiently while consuming less communication overhead.